The Influence of Profitability Liquidity, Leverage and Growth on Dividend Policies and Free Cash Flow as Moderating Variable In The Companies Listed on The Indonesia Stock Exchange Year 2015-2017 - Situmorang, Humala (Fundamental Management Journal, 2020)
One of the objectives of investors to invest is to increase their wealth. Added wealth is obtained through dividends distributed by company management. Management’s decision to divide dividends (dividend policy) is an attraction for investors to buy company shares even at high prices so that it will strengthen the company’s cash position to be used to run company operations with the aim of gaining high profits and increasing company value. The high value of the company will make it easier for management to raise funds. Logically high profits will produce high liquidity, with high liquidity in addition to being able to pay off all of its obligations as well as being able to finance the growth of the company and set aside free cash to be distributed to shareholders as dividends. Therefore the purpose of this study is to examine whether free cash flow can strengthen or weaken profitability, liquidity, leverage and growth towards management policies to pay dividends. Using a sampling purpose, the company’s sampling consists of 31 companies listed on the Indonesia Stock Exchange in 2015-2017. For testing used logistic regression analysis consisting of logistic regression test, significant test of fit model with the approach of maximum likelihood method and partial test and model formation. The results of this study indicate that free cash flow cannot encourage / strengthen the influence of profitability, liquidity, leverage and growth on dividend policy, so that profitability, liquidity, leverage and growth have no effect on dividend policy. Keywords: Profitability, liquidity, leverage, growth, free cash flow and dividend policy.